Snake Eyes [videorecording (DVD)] : G.I. Joe origins - Golding, Henry, 1987-; Koji, Andrew, 1987-; Weaving, Samara, 1992- (Paramount Home Entertainment, 2021)
A G.I. Joe spin-off centered on the character of Snake Eyes, a tenacious loner who is welcomed into an ancient Japanese clan. But his honor and allegiance will be tested, even if that means losing those closest to him.